Radiocarbon-derived ages of carbon in live, dead, and newly emerged fine roots in a cool-temperate Japanese beech forest - Koarashi, Jun; Atarashi-Andoh, Mariko; Ishizuka, Shigehiro; Noguchi, Kyotaro; Kadono, Atsunobu; Nakayama, Masataka (Frontiers in Forests and Global Change, 2025)
Forest ecosystems play a crucial role as natural carbon (C) sinks, and preserving this function is key to mitigating climate change. However, the forest C dynamics, particularly those related to the production and turnover of fine roots (<2 mm in diameter), remain largely unclear. Here, we examined the age of C in fine roots in a cool-temperate Japanese beech forest by measuring the natural abundance of radiocarbon (14C). Root samples were collected and categorized by diameter size class and live/dead status. Newly emerged roots were also obtained using an ingrowth mesh bag method. The mean ages of C in existing fine roots were estimated to be 5–23 years for live roots and 1–34 years for dead roots, respectively. In contrast, the 14C signatures of newly emerged roots indicated the use of current-year photosynthetic products for new root production. Given the negligible time lag between photosynthetic C fixation and the use of the fixed C for new root production, the observed ages for live fine root C suggest that plants use current-year photosynthetic products to produce new roots but utilize older (14C-enriched) internally stored C to support subsequent root growth, and/or that some fine roots live for many years. The age of live fine root C increased with diameter size class and branch order in branching root systems, supporting both of these processes. Our results provide a piece of knowledge to comprehensively understand belowground C allocation processes in plants and highlight that tracking changes in the 14C signature of fine roots, as well as root biomass, in relation to root development stages would be beneficial for separating these processes and quantifying the heterogeneity of fine root dynamics, encompassing both ephemeral and long-lived roots.